CURRENT ASPECTS OF SURGICAL TREATMENT OF ULCERATIVE COLITIS - Nazira U. Aripova ,; Doniyor.A. Umarov , (Central Asian Journal of Medicine, 2025)
Issues concerning the surgical treatment of patients with severe forms of ulcerative colitis (UC) currently attract the attention of surgeons worldwide. This is due not only to the increasing number of cases but also to the lack of a unified opinion on surgical tactics. The rapid progression of the disease, reevaluation of conservative treatment possibilities, and unclear indications for surgery often lead to delays in surgical intervention. At the same time, extensive resection of the colon in patients at the terminal stage of intoxication and metabolic disturbances is accompanied by a high frequency of postoperative complications (50-80%) and mortality rates (15.5-60%).